Hubungan Tingkat Kecemasan dengan Tekanan Darah pada Lansia di UPT Pelayanan Sosial Tresna Werdha-Bondowoso - Putri, Inka Mawardi; Rasni, Hanny; Muhammad Nur, Kholid Rosyidi (Pustaka Kesehatan, 2023)
An increase in Age Life Expectancy results in an increasing number of elderly. When entering the elderly, a person will experience an aging process accompanied by physiological changes that can cause reactions in the cardiovascular system, such as changes in blood pressure. Changes in blood pressure can be caused by various factors, one of which is anxiety. Anxiety is an emotional response to a judgment that describes a state of worry, anxiety, and fear. This study aims to analyze the relationship between anxiety levels and the blood pressure status to the elderly in the Pelayanan Sosial Tresna Werdha Bondowoso (UPT). The research design applies analytic correlation with a cross-sectional approach to 67 respondents. Data collection uses the Geriatric Anxiety Inventory (GAI) questionnaire from April 23 to May 23, 2019. Research Ethics Test number to be No.367 / UN25.8 / KEPK / DL / 2019. The analysis of research data using Spearman with a 0.05 significance level. The results of the anxiety level showed as many as 39 elderly (58.2%) experienced anxiety, while 28 elderly (41.8%) did not experience anxiety, with a blood pressure value of at most high normal blood pressure. There is a relation between anxiety level and blood pressure status in Pelayanan Sosial Tresna Werdha (PSTW) Bondowoso(p-value = 0.002; r = 0.369). Other factors such as age, gender, depression, stress, drugs, and physical activity need to be studied to avoid high blood pressure in the elderly.